2018
DOI: 10.1063/1674-0068/31/cjcp1805118
|View full text |Cite
|
Sign up to set email alerts
|

Ester-Derivatized indoles as fluorescent and infrared probes for hydration environments

Abstract: Tryptophan derivatives have long been used as site-specific biological probes. 4-Cyanotryptophan emits in the visible region and is the smallest blue fluorescent amino acid probe for biological applications. Other indole or tryptophan analogs may emit at even longer wavelengths than 4-cyanotryptophan. We performed FTIR, UV-Vis, and steady-state and time-resolved fluorescence spectroscopy on six ester-derivatized indoles in different solvents. Methyl indole-4-carboxylate emits at 450 nm with a long fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…8.8 ns in water. 38 Taken together, these findings suggest that the amino acid counterparts of these indole derivatives could find useful applications in biological spectroscopy and microscopy. For example, the fluorescence property of 4CO 2 H-Trp may exhibit a strong dependence on pH, due to its carboxyl group.…”
Section: ■ Effect Of Substitution In the Indole Ring On The Fluoresce...mentioning
confidence: 86%
See 4 more Smart Citations
“…8.8 ns in water. 38 Taken together, these findings suggest that the amino acid counterparts of these indole derivatives could find useful applications in biological spectroscopy and microscopy. For example, the fluorescence property of 4CO 2 H-Trp may exhibit a strong dependence on pH, due to its carboxyl group.…”
Section: ■ Effect Of Substitution In the Indole Ring On The Fluoresce...mentioning
confidence: 86%
“…Other Derivatives. The studies of Huang et al 38 and of Micikas et al 46 showed that the absorption and emission spectra of 4CO 2 H-indole and 4CO 2 Me-indole are further red-shifted from those of 4CN-indole. Moreover, both indole derivatives have a fairly large fluorescence QY (0.4−0.5) in protic solvents, 38,46 and 4CO 2 Me-indole has a fluorescence lifetime of ca.…”
Section: ■ Effect Of Substitution In the Indole Ring On The Fluoresce...mentioning
confidence: 97%
See 3 more Smart Citations